A Novel Homozygous Missense Mutation (Ile583Asn) in a Consanguineous Marriage Family with Hereditary Factor XII Deficiency: A Case Report - Jiang, Shuting; Chen, Yuan; Xie, Haixiao; Liu, Meina; Zheng, Xiaoyong; Wang, Mingshan (Hämostaseologie, 2022)
Background Hereditary coagulation factor XII (FXII) deficiency is an autosomal recessive disorder. At present, the contribution of severe FXII deficiency to the development of thromboembolism is still undetermined. There are limited reports on the relationship between the FXII defect and thromboembolism.Case Presentation A 27-year-old woman came to our hospital for the treatment of shoulder trauma and cervical disc herniation caused by a car accident. The shoulder trauma was treated with five stitches. After physical examination, imaging examination, and routine coagulation examination, cervical disc herniation was treated conservatively. Combined with the examination results, the patient was diagnosed with FXII deficiency. Unfortunately, the patient was readmitted 10 days after the trauma with edema in the lower limbs and secondary varicose veins. The D-dimer increased to 6.22 mg/L. Thrombus in the inferior vena cava and right common iliac was shown by lower limb venography. According to the patient's medical history, the F12 gene was analyzed by direct sequencing. The patient was also screened for other thrombotic risk factors. Genetic analysis showed that the patient had a c.1748T > A (p.Ile583Asn) homozygous missense mutation in exon 14 of the F12 gene. No other hereditary thrombophilia risk factors screened were positive in the patient.Conclusion The p.Ile583Asn missense mutation in exon 14 of the F12 gene might be responsible for the reduction of the FXII level in the patient.
Keywords: factor XII deficiency; gene mutation; venous thromboembolism; bioinformatics